Diagnostic and Therapeutic Approaches for a Diabetic Patient Presenting with Secondary Syphilis and Severe Odynophagia - Bramantono Bramantono; Henry Sutanto; Hermawan Susanto; Muhammad Vitanata Arfijanto; Usman Hadi (Medicina, 2024)
Syphilis, an infectious disease caused by the spirochete Treponema pallidum, represents a pervasive global epidemic. Secondary syphilis is typically marked by the emergence of highly contagious mucocutaneous manifestations, including non-pruritic rashes on the palms and soles of the feet, alopecia, mucous patches, and condyloma lata. Here, we report a rare case of a 30-year-old male with newly discovered type 2 diabetes mellitus who presented with severe odynophagia due to secondary syphilis, confirmed by both nontreponemal VDRL/RPR and treponemal TPHA tests. Following the administration of a single-dose intramuscular injection of benzathine penicillin G 2.4 million units, the symptoms gradually decreased, allowing the patient to regain his health.